THE EFFECTIVENESS OF EXTENSIVE READING APPROACH TO IMPROVE STUDENTS’ READING COMPREHENSION - Andi Hidayat; Anita Nurinayah (PROJECT (Professional Journal of English Education), 2018)
This research entitled the effectiveness of extensive reading approach has a purpose to figure out the effectiveness of extensive reading approach to improve students’ reading comprehension. The subject of this research is students of SMK Al-Irsyad Cipanas. The sample of this research consists 20 of the eleventh grade students of AP class. The research uses quantitative research, or more specifically the one group pre-test post-test design as research design. To collect the data, this research applies pre-test and post-test as the instrument. The result of data is obtained by using t-test formula.  The result showed that students who learning using extensive reading approach had better reading ability to comprehend the text. The result of tobs is 2.08, the ttable with degrees of freedom (df) 19 and level of significance at 0.05 was 1,72. Based on the data analysis, the alternative hypothesis in this research was accepted because tobs is higher than ttable (2.08 > 1.72). Based on the data analysis, it is found that the test is reliable. The findings indicated that learning using extensive reading approach is significantly affected the students’ reading comprehension. Therefore, the extensive reading is suitable for improving students’ reading comprehension and it is also a strategy that can be used by teacher for making learning process to be more effective.